Study of phenotypic and cytotoxic properties of erythroid cells of the spleen under hematopoiesis-stimulating effects - Yu. A. Shevchenko; K. V. Nazarov; S. V. Sennikov (Медицинская иммунология)
In recent years, research has revealed a wide variety of erythroid cell functions, including modulation of innate and adaptive immune responses. Anemic or hypoxic stress stimulates a physiological response in the form of stress erythropoiesis, aimed at increasing oxygen delivery to tissues. Stress erythropoiesis activates progenitor cells and uses mechanisms that differ from stationary bone marrow erythropoiesis. To consider the role of erythroid cells in the regulation of hematopoiesis, hematopoiesis-activating states were modeled: chemically induced hemolytic anemia, acute blood loss, hypoxia. A series of experiments was carried out on first-generation hybrid mice CBA C57Bl6. Isolation of erythroid cells was performed using magnetic separation for the CD71 marker. The stages of differentiation of erythroid cells were determined by the combination of expression of TER-119 and CD71 markers and direct light scattering parameters in the population of both CD45-positive and CD45-negative spleen cells. To study the immunoregulatory activity of erythroid cells, we investigated the mediated cytotoxicity of splenocytes against tumor cells of the mouse melanoma B78 line after cultivation with conditioned spleen media after various hematopoiesis-stimulating effects. With various hemopoiesis-stimulating effects, the quantitative and qualitative composition of the spleen cells is reorganized depending on the compensatory mechanism for restoring homeostasis. An analysis of the cellular composition of the spleen showed that under hematopoiesis-stimulating effects, a redistribution of populations with the CD45 marker occurs: during hypoxia, the number of CD45-negative cells sharply decreases and the number of CD45-positive cells increases. The population of basophilic erythroblasts is the least susceptible to quantitative changes under all hematopoiesis-stimulating effects. During hypoxia, the most noticeable change in the cellular composition of the spleen is observed due to the increased accumulation of CD45-positive erythroid cells in the spleen. Mediators of erythroid cells of the spleen of mice after hypoxia do not lead to an increase in the cytotoxic proapoptotic effect of splenocytes on tumor cells, in contrast to the erythroid cells of the normal spleen, spleen with anemia and blood loss. Thus, it is tissue hypoxia that is the process that not only stimulates erythropoiesis, but also leads to the maximum change in the suppressive properties of surrounding cells. We assume that the implementation of compensatory mechanisms under the studied hematopoiesis-stimulating effects is aimed at activating the mechanisms of innate immunity and local immunosuppression to prevent local inflammation, accumulate nutrients, and attract cellular elements to the focus of hematopoiesis to restore homeostatic functions.